Upaya Guru BK Dalam Mengubah Persepsi Negatif Murid Mengenai Guru BK - Amanda Rosa; Nela Yusniarti; Mutiah; Timi Krismonia (JPT : Jurnal Pendidikan Tematik, 2023)
Every individual has a different perception. And each perception can have a positive or negative side. By understanding a person's perception, we can gain a picture of how the individual might respond to an object or situation they face. Humans are social creatures, who need each other. Guidance and counseling is a form of assistance between clients and counselors to address the problems they experience. Guidance and counseling teachers in schools certainly have a role in helping students develop their potential and also in addressing ongoing problems. However, from ancient times to the present, our observations in the field have often encountered cases such as students being afraid of guidance and counseling teachers. Therefore, we are conducting this research to change students' perceptions of guidance and counseling teachers. This research falls into the category of qualitative research. Literature review is the method used for data collection. Through literature searches using various scientific sources, including books, theses, papers, scientific articles, and literature related to the research topic, data or literature sources are collected. Therefore, the role of the guidance and counseling teacher in changing this perception is very important. The role played by the guidance and counseling teacher to change students' negative perceptions of the guidance and counseling teacher is: Trying to get close to students, being friendly to students, explaining to students about guidance and counseling, and giving rewards or awards to students.